Pre-Jurassic evolution of the Fingerdjupet Subbasin, SW Barents Sea - Norkus, Audrius (2015)
The Fingerdjupet Subbasin is N-S trending basin in the western Barents Sea, which developed as a westward tilted halfgraben in the hanging-wall of a basin-bounding listric normal normal fault as a response to the extension in the North Atlantic during the Late Paleozoic. Thick succession from Carboniferous to Triassic contains complex geological evolution and using partial well control was examined during this study. This thesis describes the pre-Jurassic structural and stratigraphic framework of the Fingerdjupet Subbasin. The interpretation of the 2D seismic lines was carried out using both software and paper method to obtain the detailed structural evolution of the basin and relate it to the sediment infill. Six seismic key lines were selected to represent the main structural and stratigraphic observations in the Fingerdjupet Subbasin. Based on the detailed interpretation of the succession from mid Carboniferous to Early Cretaceous, three megasequences were defined and described in detail to reconstruct the evolution of the basin through time. Based on megasequences time-thickness maps were created to study the lateral and vertical changes in the geometries and depositional patterns. These maps are presented together with time-structure maps with interpreted faults in order to relate the basin infill with the observed tectonic regimes in the area. Finally, the pre-Jurassic geological evolution is discussed with the focus on a regional setting and surrounding areas to recover the Fingerdjupet Subbasin evolution. During the Late Paleozoic times, the Fingerdjupet Subbasin might have experienced three different extensional regimes. These were dated to be of Devonian (?), mid Carboniferous and late Permian age. Gabrielsen et al. (1990) suggested that the Fingerdjupet Subbasin formed during the Early Cretaceous due to the extension in the North Atlantic. However, after this study it can be suggested that the onset of the formation was in late Permian.